TESOL in the New Era: Introduction to the 2021 Global English Education China Assembly Special Issue - Rining (Tony); Jim Hu (Cranmore Publishing, 2021)
Welcome to the International Journal of TESOL Studies (IJTS) special issue for the 2021 Global English Education China Assembly (henceforth "the Assembly"). This is the first of the three special issues of the 2021 Assembly (see also the Call for Papers at the end of this volume). Organised by China Daily in partnership with TESOL International Association, the Assembly is a high-level international English Language Teaching (ELT) event in China. The 2021 Assembly held in July in Hangzhou (Zhejiang Province, China) brought together over 3,000 attendees, both on site and online. They were ELT practitioners, scholars, and researchers in China and from abroad. On the Assembly platform, they exchanged experiences and views and shared research outputs. We are in a new era where one of the world's largest disruptions to daily life is still on-going. Despite the stress everyone is facing during the pandemic, contributors have been productive. As Guest Editors, we feel honoured and pleased to introduce the works of 17 scholars (including two prestigious interviewees) that appear in this volume. Prior to our introduction, we need to congratulate these fine scholars for their work completed successfully in the new era. This special issue features 11 papers from TESOL experts, researchers, and practitioners based not only in China but also in other countries including Canada, the UK, and the USA. These 11 papers are followed by two interviews respectively with two renowned scholars conducted by Ms. Peng Lun, Editor-in-Chief of the Assembly Special Issues. These papers use a wide variety of approaches, ranging from experimental designs, corpus-based methods, survey-based studies, case studies, to mix-methods research.